HUBUNGAN KESEHATAN MENTAL DENGAN PENYESUAIAN DIRI PESERTA DIDIK DI SMP MUHAMMADIYAH 6 PADANG - Tiyaningsih, Trilis; Kasih, Fitria; Zaini, Ahmad (Bimbingan dan Konseling, 2013)
The problems in this research is relationship of mental health with the adjustment of students in SMP Muhammadiyah 6 Padang. The purpose of this study are : 1. View an illustration of mental health of students. 2. View an adjusment of students. 3. View a relationship between  mental health and adjustment of students. This research is correlational description that attempted to describe the phenomenon specific events in detail, systematically, and it is in accordance with the facts and then sought the context.  its population are students in SMP Muhammadiyah 6 Padang which amount to 373 students. Samples in this study of 40 students. Sampling techniques used stratified random sampling. Instruments used in this study are questionnaire. For the analysis of data correlation or relationship by using the correlation tests of products moment. The Results of this study is 1. An illustration of mental health the students in SMP Muhammadiyah 6 Padang are in good condition. 2. An illustration of adjustment  the students in SMP Muhammadiyah 6 Padang also are in good condition. 3. The relationship of mental health with adjustment of students is very strong relationship. Based on the researcher finding are expected to all school personnel in order to create the harmonious condition, balanced, and comfortable throught the development of mental  health of students, so students can easily to do a good adjustment in school, and can be able to expand their talent as much as possible.